Fragile Familien Ehe und häusliche Lebenswelt in der bürgerlichen Moderne - Eibach, Joachim (De Gruyter, 2022)
This book presents a new history of the family in the era of bourgeois modernity. The sources it uses are personal accounts, first and foremost diaries, but also letters and autobiographical texts from eight German-speaking families from different milieus.